1985
DOI: 10.1107/s0108768185001525
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of KLiSO4 as a function of temperature

Abstract: A crystal structure investigation focused on the thermal motion of O and Li and based on single-crystal X-ray diffraction data (Mo Ka) has been carried out at 293, 398 and 568 K in space group P63 with the assumption of complete atomic order. Anharmonic temperature factors based on the Gram-Charlier expansion have been refined up to the third order for O and Li with about 600 observed Fo values (Rw = 0.017-0.024). Probability densities (O, Li) and oneparticle potentials have been calculated from the coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…The splitting of both O(1) and 0(2) into three sites means that the rigid SO 4 tetrahedra are disordered in three positions with equal probability, which is rather similar to the results at room temperature reported by Schulz et al (1985).…”
Section: Ok ©Osupporting
confidence: 86%
See 2 more Smart Citations
“…The splitting of both O(1) and 0(2) into three sites means that the rigid SO 4 tetrahedra are disordered in three positions with equal probability, which is rather similar to the results at room temperature reported by Schulz et al (1985).…”
Section: Ok ©Osupporting
confidence: 86%
“…By contrast, BhakayTamhane, Sequeira & Chidambaram (1984)treated O(1) atoms, which form the vertices of the tetrahedra, as occupying threefold split positions with occupancy of 1/3. Schulz, Zucker & Frech (1985) found that both oxygens show large and strongly anharmonic thermal motion as well as static disorder. They explained the thermal vibration as the coupled rotational vibration of the oxygens around the S atoms.…”
Section: * Data From Wyekoff (1968)mentioning
confidence: 99%
See 1 more Smart Citation
“…KLiS04 (j). Schulz, Zucker & Frech (1985) have determined this structure between room temperature and 568 K. It consists of a relatively flexible framework of corner-shared LiOn and SOn tetrahedra with nine-coordinated K filling the cavities within the framework.…”
Section: Mgge03 Clinopyroxene (I)mentioning
confidence: 99%
“…The structure was included because it is the only one, apart from LilO3, that contains bonds with valences less than 0.2 v.u. The contraction of the S---O bonds on heating can be ascribed to the librational motion of the rigid SOn groups, although when Schulz et al (1985) corrected the bond lengths for libration, a significant contraction remained for S--O1, an effect they attribute to anharmonic librations that are not included in the normal riding model correction (Busing & Levy, 1964). Given the uncertainties inherent in both the theoretical and experimental values for this compound, the agreement is satisfactory.…”
Section: Mgge03 Clinopyroxene (I)mentioning
confidence: 99%